The hundred most frequently cited studies on sleeve gastrectomy - Stefura, Tomasz (Wideochir Inne Tech Maloinwazyjne, 2019)
INTRODUCTION: Sleeve gastrectomy (SG) is one of the most popular bariatric operations and one of the most frequently studied areas in bariatric surgery. AIM: To summarise the characteristics of the most frequently cited studies focusing on SG. MATERIAL AND METHODS: We used the Web of Science database to identify all studies focused on SG published from 2000 to 2018. The term “sleeve gastrectomy” and synonyms were used to reveal the 100 most cited records. RESULTS: The most frequently cited publication had 493 citations. The highest mean number of citations per year was 73.00. Studies were most frequently published in the years 2010 and 2012. Articles were most commonly published in bariatric surgery-oriented journals. CONCLUSIONS: Our study indicates an increase in medical researchers’ interest in the subject of SG and underlines the need to perform studies with a higher level of evidence to further analyse the outcomes and basic science behind SG.